Karakter Pendidikan untuk Membentuk Pendidikan Karakter - Jalil, Abdul (Nadwa, 2012)
Existence of madrasa over time increasingly eroded by the waves leveling on behalf of accreditation. As an initiative to defend against scour vision of civiliza-tion, educational institution of Qudsiyyah finally returned to khittah to establish Mahad Qudsiyyah in Kudus which concentrates on aspects of ulu>mul fiqh. Goals to be achieved is a man of character formation intact (al-Kaun al-jami>) and the balance between mind and heart, body and spirit, skill and character, as well as cognitive, affective and psychomotor. Mahad Qudsiyyah have set up processes and educational management that reflects management measures, implementation strategies, readiness of human resources of education and edu-cation, indicators of success of the program, design a comprehensive program contains content and contextual analysis of the educational process, technical evaluation and monitoring programs and policy formulation.